Can Systematic Justice Be Achieved for Parents with Intellectual Disabilities in Deprivation of Custody Cases? - Hanna Björg Sigurjónsdóttir; James Gordon Rice (Disabilities)
This case report is a reflection on the cumulative results of a number of research projects conducted in Iceland in the field of parenting with a disability. The underlying research consisted primarily of an analysis of court case documents and interviews with parents, extended family members and relevant professionals. The contribution that follows emerged out of a question that we posed to our overall research findings and experiences—what does justice look like for parents with ID who have to contend with deprivation of custody orders? In the rare instances in which a parent ultimately prevailed over an unjust deprivation order, this was only accomplished after an extensive fight through the court system, after which, a great deal of harm to the family had already been caused. We offer for consideration a close look at one such case that we followed, the aftereffects of which are still ongoing. The other path to success appears to be that of early intervention, but this typically occurs through happenstance and requires the involvement of a network of progressive professionals and fortuitous timing. Our contribution is a call to discuss what justice looks like and how this may be transformed into something more systematic.